Pengaruh Kartu Huruf Terhadap Kemampuan Membaca Permulaan Siswa pada Mata Pelajaran Bahasa Indonesia Kelas II di Sekolah Dasar - Anggi Putri Wahyuni; Sahkholid Nasution; Muhammad Syaifullah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to determine the effect of the use of letter card media on students' initial reading ability in Indonesian Language subject grade II in elementary school. This research is a quantitative research with an experimental research method with a quasi experiment type. The sample of this study was taken using a saturated sampling technique consisting of two classes, namely class II A with 20 students as a control class without using letter cards and class II B with 20 students as an experimental class using letter card media. The data collection technique used in this study is a performance test (initial reading test) using pretest and posttest. The results of the research from both classes, namely in the pretest, had an average value (Mean) of the experimental class of 52.50 and the control class of 49.69. At the time of the posttest, the average score (Mean) of the experimental class was 80.94 and the control class was 59.69. The results of the hypothesis show that the tcount value > the table is 5,146 > 1,684 which means that H0 is rejected and H1 is accepted. So, the hypothesis states that the letter card media has an effect on students' initial reading ability in Indonesian subjects grade II at UPT SDN 060816 Medan.